Six C's for Effective Teaching - Radhika Devi, V. (Journal of Engineering Education Transformations, 2016)
A typical college teacher preparing course Introduction: content, spends years in teaching but spends no time on development of teaching skills. When teachers think that the best way to improve their teaching is achieved only by developing their content knowledge, end up with 50% of imparting the subject knowledge. To think that content, matters more than teaching skills, is to imagine that the car ismore important than the road. But both are essential. What we teach and how we teach are inextricably linked and are very much dependent on one another. Even though both are tightly linked, development of the one doesn't automatically improve the function of the other. So far no specific attention is paid to certain of the basic requirements to achieve 100% effective transfer of knowledge. This article identifies a set of six C's, (Content, Communication, Confidence, Critical thinking, Collaboration, Creativity) for effective teaching to move from LOTS (Lower Order Teaching Skills) toHOTS (Higher Order Teaching Skills).